Botanical origin, nutritional values and probiotic properties of bee bread of stingless bee (Heterotrigona itama cockerell) - Mohammad, Salma Malihah (2020)
Bee bread is bee-collected pollen, added with honey and bee salivary enzymes. It undergoes lactic acid fermentation by indigenous microbes as it is stored inside the closed pots in the beehive. In comparison to honey, bee bread is still an underutilized bee product with limited nutrient information. This study aims to identify the botanical origin and characterize the nutritional composition of stingless bee (Heterotrigona itama) bee bread and also isolate and further characterize the probiotic potential of bacteria from the bee bread. The melissopalynology analysis using a Scanning Electron Microscope (SEM) discovered Biden pilosa in bee bread samples from all geographical locations with Asteraceae as the predominant family plant. From the proximate analysis, H. itama bee bread was found to be high in carbohydrate (58.03 ± 0.75%), protein (22.46 ± 0.63%), lipid (5.29 ± 0.53%) and ash (2.56 ± 0.13%). The sugar profile analysis using High-Performance Liquid Chromatography- Evaporating Light Scattering Detector (HPLC-ELSD) found glucose as the most abundant followed by fructose. The amino acids were quantified with HPLC-Fluorescence Detector (FLD). Eight essential amino acids were present with phenylalanine as the most abundant with 2.317 g/100 g. The mineral content and heavy metals were analyzed using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). The major mineral element was potassium (average 6705.9 mg/kg). Heavy metals such as lead, arsenic, cadmium and mercury were detected within the safe permitted levels. Ninety-seven (97) bacterial strains were isolated from H. itama bee bread. From these, 27 were presumed to be lactic acid bacteria (LAB) and Bacillus from Gram-staining and catalase test. The presumptive bacteria were identified using 16s rRNA gene sequencing. These bacteria were Lactobacillus musae, Lb. crustorum, Lb. mindensis, Leuconostoc mesenteroides, Enterococcus faecalis, Fructobacillus fructosus, Bacillus safensis, B. amyloliquefaciens, B. megaterium, B. cereus and B. pumilus. The bacteria were evaluated for its hemolytic ability on 5% blood sheep agar. All LAB strains and B. megaterium MPS2 did not hemolyzed blood. Antagonistic activities against foodborne pathogens using agar well diffusion showed L. musae SGMT17 and L. crustorum SGMT22 with the highest inhibition zone, comparable to those of commercial strains Lb. rhamnosus GG. The bacteria with antibacterial properties were assessed for their viability in pH 3, 0.3% bile and digestive enzymes. All strains were able to tolerate the simulated conditions except for F. fructosus U45 and U47 as they recorded viability below 80% after treatment in pepsin and pancreatin simultaneously. The adhesion properties using autoaggregation and cell surface hydrophobicity (CSH) demonstrated L. mindensis SGMT22 with highest autoaggregation ability (41.16%) while Lc. mesenteroides U39 showed the highest CSH (80.52%). The antibiotic resistance patterns for the isolates against 11 antibiotics were assessed using the disc diffusion method and interpreted using standard of Clinical and Laboratory Standard Institute (CLSI). All strains were susceptible to chloramphenicol, ampicillin and tetracycline, but varied for eight antibiotics. From the result obtained, Lb. musae SGMT17 and Lb. crustorum SGMT20 showed the highest antibacterial activity and probiotic properties in the human in vitro digestive model. The outcomes of this study contribute towards the knowledge on the nutritional information of H. itama bee bread, its potential as commercialize food or food ingredients.